Avaliação da toxicidade aguda e da atividade gastroprotetora de extratos de Campomanesia lineatifolia Ruiz & Pav. em roedores - Raquel Cenachi Madalosso (2011)
The Campomanesia lineatifolia Ruiz & Pav. (Myrtaceae), popularly known as gabiroba, is a native species of the Amazon region used in traditional medicine for treating gastrointestinal disorders. In previous studies, the ethanolic extract (EEC) and ethyl acetate fraction (EAFC) showed in vitro antioxidant activity and the phytochemical profile reveled the presence of tannins and flavonoids. Catechin and quercitrin were also isolated and identified. However, there are no studies providing safety and pharmacological in vivo data for this species. In the present study, the acute toxicity and gastroprotective activity of EEC and EAFC were evaluated. The acute oral toxicity study was performed according to the method of classes with starting dose of 2000 mg/kg (OECD 423). The gastroprotective activity of EEC or EAFC was investigated in rats with ethanol (5 mL/kg, p.o.) induced gastric lesion at doses of 100, 200 or 400 mg/kg (p.o.) and in rats with indomethacin (40 mg/kg, p.o.) induced acute gastric lesion, at doses of 400, 800 or 1200 mg/kg (p.o.) The hemorrhagic zones and regions of necrosis were assessed by using morphometric analysis. The mucus content was estimated by using periodic acid of Schiff stain. EEC and EAFC were found to be safe in acute toxicity test. The extracts significantly decrease lesion area in both models in a dose dependent-manner, which demonstrates their gastroprotective activity as compared to standard drugs sucralfate and cimetidine. The better response of EAFC, in ethanol model, and of EEC, in indomethacin model, suggest that more than one mode of action may be involved. AEFC 400 mg/kg significantly replenished the ethanol-induced depleted levels of gastric mucus. EEC and EAFC gastroprotective activity is possibly mediated through enhance of gastric mucosal defense mechanisms. The results contribute to the validation of the ethnopharmacological data of C. lineatifolia. Keywords: Campomanesia lineatifolia, Myrtaceae, acute toxicity, gastric ulcer, gastroprotective, gastric mucus